New species and distributional records of the genus Broscosoma Rosenhauer, 1846 (Coleoptera, Carabidae, Broscinae) from Fujian, China - Jiang, Ri-Xin; Chen, Xiang-Sheng (Zootaxa, 2023)
A new species of the genus Broscosoma Rosenhauer, 1846 is described from Fujian Province, China. New distributional records of Broscosoma guoliangi Jiang, Liu & Wang, 2021 are added. Distributional map of known Broscosoma species from Fujian Province and the key to Broscosoma species from Southeast China are also provided.